2016
DOI: 10.1002/aic.15193
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐fuel scaled‐down autothermal pure H2 generator: Design and proof of concept

Abstract: This article presents experimental results of an autothermal scaled‐down system for H2 production. Pure atmospheric pressure H2, separated in situ by Pd–Ag membranes, is produced by steam reforming (SR) of methane, ethanol, or glycerol. Oxidizing the SR effluents in a separate compartment supplies the heat. The oxidation feed is axially distributed to avoid hotspots. The 1.3 L system, comprises 100 cm2 of membrane area, and generates H2 flow rate equivalent to 0.15 kW at an efficiency of ∼25%. This process lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In any case, it has been shown that the apparent permeance can be considerably smaller than the one measured in pure hydrogen, even after accounting for dilution, concentration gradients, and inhibition. The occurrence of hydrogen-consuming reactions on the surface of the membrane has also been proposed as a possible reason for the drop in the observed hydrogen flux [ 5 , 32 , 112 ] and may strongly affect the reactor performance.…”
Section: Constitutive Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, it has been shown that the apparent permeance can be considerably smaller than the one measured in pure hydrogen, even after accounting for dilution, concentration gradients, and inhibition. The occurrence of hydrogen-consuming reactions on the surface of the membrane has also been proposed as a possible reason for the drop in the observed hydrogen flux [ 5 , 32 , 112 ] and may strongly affect the reactor performance.…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…Membrane reactors (MRs) have received significant attention for their potential use in decentralized hydrogen production systems, allowed by the integrated production and separation of hydrogen [ 1 , 2 , 3 ]. The reactions most commonly carried out are those of steam reforming of different carbon-based feeds such as methane [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], methanol [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ], ethanol [ 22 , 23 , 24 , 25 , 26 , 27 ], biogas [ 28 , 29 ], and glycerol [ 30 , 31 , 32 ]; water-gas shift [ 33 , 34 , 35 , 36 , 37 , 38 ]; ammonia decomposition [ 39 , 40 ]; and the dehydrogenation of alkanes [ 41 , 42 , 43 , 44 ]. In all cases the equilibrium of the reaction is shifted by removing hydrogen through a membrane.…”
Section: Introductionmentioning
confidence: 99%